Pengetahuan Dasar-Dasar Hukum Bisnis Di Indonesia - Fajar Ahmad Kurnia; Alya Maisyarah; Jepi Haris Munandar; Adzra Oktalismanriva (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
Consumers are often the parties who rarely pay attention to their interests, where the form of legal assistance is very weak and not guaranteed as expected. Indonesia is a developing country that continues to carry out development in all fields, both in the material and spiritual fields, where this development aims to realize the goal of developing a just and prosperous society, one of the developments in the material sector is including facilities and infrastructure such as the construction of housing, both on a luxurious scale, middle class, even down to housing for the people (subsidized). In this research, the problem is how the developer fulfills its obligations to consumers who have made payments. This approach method is used to find out what the overall, complete and systematic implementation of banking mediation is like. Meanwhile, the nature of the research used in this writing is descriptive, namely by drawing conclusions from a general problem regarding the concrete problem being faced, then the existing legal material is analyzed to see whether it can answer the problems raised by providing an overall picture. Keywords: Agreement, credit agreement, housing procurement